2012
DOI: 10.1016/j.atmosenv.2012.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Saharan dust impact in central Italy: An overview on three years elemental data records

Abstract: h i g h l i g h t s< PIXE is very effective to quantify the actual mineral dust contribution to PM. < The impact of Saharan intrusions on PM10 is extremely variable from case to case. t r a c tIn southern European countries, Saharan dust may episodically produce significant increases of PM10, which may also cause the exceedance of the PM10 daily limit value established by the European Directive (2008/50/EC). The detection with very high sensitivity of all the elements that constitute mineral dust makes PIXE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 37 publications
1
54
1
Order By: Relevance
“…Specifically, the following parameters were examined with respect to the calculation of net African dust: (i) the identification of dust transport episodes by different modelling tools; (ii) the use of PMF analysis for the identification of a mixed mineral dust source or a separate African dust source; (iii) the use of alternative input concentration data, such as the coarse PM fraction (PM 2.5−10 ) and the mineral component of PM 10 , calculated either by PMF analysis or reconstructed from elemental concentrations based on stoichiometry (Nava et al, 2012;Marcazzan et al, 2001): …”
Section: Sensitivity Analysis On the Estimation Of African Dust Contrmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the following parameters were examined with respect to the calculation of net African dust: (i) the identification of dust transport episodes by different modelling tools; (ii) the use of PMF analysis for the identification of a mixed mineral dust source or a separate African dust source; (iii) the use of alternative input concentration data, such as the coarse PM fraction (PM 2.5−10 ) and the mineral component of PM 10 , calculated either by PMF analysis or reconstructed from elemental concentrations based on stoichiometry (Nava et al, 2012;Marcazzan et al, 2001): …”
Section: Sensitivity Analysis On the Estimation Of African Dust Contrmentioning
confidence: 99%
“…The Mediterranean climate, characterised by increased solar radiation and low rainfall rates, promotes aerosol production and reduces the potential for dispersion and removal of pollutants (Lazaridis et al, 2005). The vicinity of southern Europe to North Africa on the other hand results in frequent and intense dust outbreaks, with high loads of dust from desert regions transported across the Mediterranean, which often leads to exceedances of air quality limit values (Pey et al, 2013;Nava et al, 2012;Athanasopoulou et al, 2010;Querol et al, 1998Querol et al, , 2009Gerasopoulos et al, 2006;Kallos et al, 2006;Rodriguez et al, 2001).…”
mentioning
confidence: 99%
“…In order to quantify the impact of Saharan dust intrusion episodes on PM 10 concentrations, the mineral content was estimated as the sum of the contributions of all the main crustal element oxides (SiO 2 , Al 2 O 3 , Fe 2 O 3 , CaO, Na 2 O, MgO, K 2 O, TiO 2 ), following the approach reported in the literature by several authors (Eldred et al, 1987;Malm et al, 1994;Miranda et al, 1994;Marcazzan et al, 2001;Nava et al, 2012): [Ti]. Some corrections, however, were applied to this formula to take into account the sea-salt contributions to Na, Mg, K, and Ca, which may be relevant at Lampedusa, and possible anthropogenic contributions to the other elements.…”
Section: Dust Contribution To Pm 10mentioning
confidence: 99%
“…Intense dust transport episodes may cause health impacts due to the high levels of PM, with which transport of anthropogenic pollutants may be associated (Erel et al, 2006). Thus, many recent studies have focused on the estimation of the influence of African dust on air quality in southern European countries, especially Spain and Italy (Rodríguez et al, 2001;Escudero et al, 2007;Perrino et al, 2008, Nava et al, 2012. Recent analyses by Kallos et al (2007) and Astitha et al (2008) have shown that, in the period 2001-2005, desert dust is present in approximately 50 % of the days in which the PM 10 EU limit is exceeded.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral dust was chemically reconstructed by using the elemental concentrations of the crustal species Al, Si, Ti, and Fe plus non sea salt fraction of Na, Mg, Ca, and K, all multiplied by factors to convert them to their common oxides. More specific soil dust was calculated as: 1.35 * Na + 1.66 * Mg + 1.89 * Al + 2.14 * Si + 1.21 * K + 1.4 Ca + 1.67 * Ti + 1.43 * Fe (Nava et al, 2012). Because Al, Si, and Ti concentrations were not determined by ET-AAS, they were estimated from the remaining known mineral components, based on the typical ratios for the site, calculated from XRF measurements.…”
Section: Calculation Of Mineral Componentmentioning
confidence: 99%